Discriminative quadratic feature learning for handwritten Chinese character recognition. (January 2016) - Zhou, Ming-Ke; Zhang, Xu-Yao; Yin, Fei; Liu, Cheng-Lin
Abstract: In this paper, we propose a feature learning method for handwritten Chinese character recognition (HCCR), called discriminative quadratic feature learning (DQFL). Based on original gradient direction feature representation, quadratic correlation between features is used to promote the feature dimensionality, then discriminative feature extraction (DFE) is used for dimensionality reduction. By combining dimensionality promotion and reduction, we can learn a much more discriminative and nonlinear feature representation, which can then boost the classification accuracy significantly. For dimensionality promotion, two types of correlation are exploited, namely, statistical correlation and spatial correlation. Statistical correlation is computed on multiple local feature vectors in different regions of the character image; while spatial correlation encodes the dependency between features of two positions. Feature correlation increases the dimensionality by over 40, 000. DFE then reduces the dimensionality to less than 300 without losing discriminability. Classification is performed using nearest prototype classifier (NPC), modified quadratic discriminant function (MQDF) and discriminative learning quadratic discriminant function (DLQDF). In experiments on the CASIA-HWDB1.1 standard dataset, the proposed DQFL method improves the test accuracies of NPC, MQDF and DLQDF by 4.94%, 1.83%, and 1.82%, respectively. The test accuracy is further improved by training set expansion. On the ICDAR 2013 Chinese handwriting recognition competition dataset, the proposed DQFL+DLQDF classifier outperforms the best participating system based on deep convolutional neural network (CNN), while the test speed is much faster. Abstract : Highlights: We propose a feature learning method for handwritten Chinese character recognition. Quadratic correlation between original gradient features is utilized. Discriminative learning guarantees the discriminability of quadratic features. The proposed method outperforms deep convolutional neural networks with much faster test speed.